Deciphering Traditional African Education in R.S. Petersâ€™ Education as Initiation - Amasa P. Ndofirepi (Journal of Education and Learning (EduLearn), 2014)
In this theoretical paper, I examine education in traditional African societies in the context of R.S. Petersâ€™ (1966) conception of â€œEducation as Initiationâ€. Philosophers of education have developed a concern and insight into the notion of education primarily by addressing the question of conceptual analysis:Â  what do we mean by education and add a justificatory question: how do we know that education is valuable? Traditional conceptions of education have viewed education as the process of initiation of new entrants into the practices of a given social group. This paper focuses special interest on the extent to which traditional African view of education is defensible within the R.S. Peterâ€™s conception of education. I draw some philosophical insights by interrogating some perspectives on indoctrination and initiation in the understanding of the notion of the aim of education.